2023
DOI: 10.5216/v.v20.71383
|View full text |Cite
|
Sign up to set email alerts
|

A/r/tógrafo Viajante: um Conceito em Construção

Abstract: Este estudo objetivou conceber significados de “a/r/tógrafo viajante” com base na literatura e nas experiências vivenciadas em expedições fotográficas preliminares de minha tese doutoral. Seguiu uma perspectiva qualitativa, de cunho exploratório e descritivo, tendo traços do método (auto)biográfico. Apresenta contribuições teóricas ainda incipientes no campo da a/r/tografia como metodologia, ao expandir sua abrangência de aplicação em distintos campos do conhecimento e elucidar sobre as possibilidades vivas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These "modern" samples enable us to extend our knowledge of the metallicity gradient and, if any, the accompanying substructure, such as the azimuthal variation traced with Cepheids. For example, Trentin et al (2023) and da Silva et al (2023) measured the chemical abundances of recently identified Cepheids located beyond 20 kpc in R GC . However, such distant Cepheids tend to be affected by high interstellar extinction and require spectroscopic measurements in the IR range instead of optical spectroscopy, which has been used in most previous works.…”
Section: Introductionmentioning
confidence: 99%
“…These "modern" samples enable us to extend our knowledge of the metallicity gradient and, if any, the accompanying substructure, such as the azimuthal variation traced with Cepheids. For example, Trentin et al (2023) and da Silva et al (2023) measured the chemical abundances of recently identified Cepheids located beyond 20 kpc in R GC . However, such distant Cepheids tend to be affected by high interstellar extinction and require spectroscopic measurements in the IR range instead of optical spectroscopy, which has been used in most previous works.…”
Section: Introductionmentioning
confidence: 99%